Governance communication and school development in Rural and remote areas of Lao PDR (The Philippine Journal of Development Communication, 2008)
This paper contributes to the current body of knowledge on development communication, governance, and education management by testing a typology of governance communication on school-based management. It applies the ideal type features of public governance communication at the community level in the case of school construction in rural and remote areas of Lao PDR. It answers the question: Are the features of community governance communication present in community-based school construction and maintenance? It sought to: determine features of community governance communication within the school construction and maintenance model; assess how governance communication is operatinalized in rural and remote communities in Lao PDR; and establish the functions of governance communication in community-based school construction and management.